Toda Raba Limited: Integrated Aquaculture Agriculture Systems - Toda, Raba, Limited (2024)
This is a proposal for Scaling Climate Smart Aquaculture Technologies to Smallholder Farmers. The project is a partnership between Toda Raba Ltd and the International Management Institute (IWMI). With a $30,000 grant, the initiative aims to integrate Climate-Smart Aquaculture Technologies into the Toda Raba business model, enabling smallholder farmers to serve as buyers of high-quality fingerlings and seed while receiving extension services tailored to clients’ needs. Toda Raba aims to build a loyal network of return customers by providing guidance on aquaculture better management practices. This includes farm visits, interactive sessions, and skill development in integrated farming techniques. Recently, the company unveiled a state-of-the-art fish hatchery that employs advanced climate-smart aquaculture technologies to produce high-quality fingerlings in a greenhouse setting, with an estimated annual output of 1.2 million fingerlings.